Studies on Seminal Enzyme (GOT, GPT and LDH) Profile and its Relationship with Acrosomal Integrity in Surti Buffalo Bull Semen - SHARMA, RAJEEV; PAREEK, P K; TAILOR, S P; PUROHIT, G N (The Indian Journal of Animal Reproduction, 2003)
Six ejaculates each from 5 Surti buffalo bulls were cryopreserved and studied before and after cryopreservation and at½, 1 and 2 hours post thawing to evaluate the extent of damage of spermatozoa. The sperm motility and percent live sperms and percent normal acrosomes showed a decline after cryopreservation. The seminal enzymes GOT, GPT and LDH increased in the seminal plasma to significanly high level (P<0.01) post freezing and thawing and at different times of post thaw incubation indicating a leakage from the spermatozoa. It was concluded that freezing and thawing of semen causes cryoinjury to the sperms, decrease in the percentage of intct acrosomes and leakage of semen enzymes.